Accuracy and precision of the measurement of liner orientation of dual mobility cup total hip arthroplasty using ultrasound imaging. (October 2022) - Riglet, Louis; Viste, Anthony; De Leissègues, Tristan; Naaim, Alexandre; Liebgott, Hervé; Dumas, Raphaël; Fessy, Michel Henri; Gras, Laure-Lise
Highlights: In vivo motion of the polyethylene liner of dual mobility cup is unclear. Liner position is studied when DMC is submerged and implanted ex vivo. Liner position is calculated using motion analysis and 3D ultrasound imaging. The study demonstrated the feasibility to analyse liners using ultrasound imaging. Abstract: The Dual Mobility Cup (DMC) was created in 1974 to prevent dislocation and decrease wear. However, the movement of the polyethylene liner in vivo remains unclear. The aims of this study were to visualise liner positions and quantify the accuracy of the liner plane orientation for static positions, using ultrasound imaging. DMC reconstruction and angle between cup and liner were evaluated on isolated submerged DMCs by comparing 3D laser scans and ultrasound imaging. Moreover, the abduction and anteversion angles of the liner plane relative to the pelvis orientation were calculated via combined motion analysis and 3D ultrasound imaging on four fresh post-mortem human subjects with implanted DMC. On submerged DMC, the mean angle error between ultrasound imaging and 3D scan was 1.2°. In cadaveric experiments, intra-operator repeatability proved satisfactory, with low range value (lower than 2°) and standard deviation (lower than 1°). The study demonstrates the feasibility of measuring liner orientation on submerged and ex vivo experiments using ultrasound imaging, and is a first step towards in vivo analysis of DMC movement.